Cut leaf assay: A rapid method for screening rust resistance in sugarcane - R, Selvakumar; T. Lakshmi Pathy; K. Gopalareddy; R. Viswanathan (Journal of Sugarcane Research, 2024)
Sugarcane rust incited by Puccinia melanocephala (brown rust) and P. kuehnii (orange rust) becomes very severe under warm,moist climatic conditions. Though there were methods to screen rust resistance under artificial conditions where rust is prevalent,there is no method to screen the rust resistance in a place where rust occurrence is not regular and severe. To overcome this problem, a simple method was devised to screen sugarcane leaves challenged with rust uredospores and maintaining the setup under optimum relative humidity and temperature for 15-20 days for identifying the rust resistant sugarcane clones. This method of rust screening is simple and easy, fast and reliable and many clones can be screened in short period of 20 days.